SOME CHARACTERIZATIONS OF 2-INNER PRODUCT - Malčeski, Risto; Anevska, Katerina; Malčeski, Samoil (Matematichki Bilten, 2017)
The characterization of 2-inner product is an issue which is the focus of interest of many mathematicians. In this paper, several equivalent characterizations of 2-inner product, that are consequences of Theorem 2 ([12]) are discussed. Thus, the equivalence of generalizations of the Jordan and von Neumann ([7]) and also Frechet ([8]) classical results, are proven. Furthermore, the characterization of Hlawka, the characterization of D. S. Marinescu, M. Monea, M. Opincariu and M. Stroe ([4]) are proven as well.